2010
DOI: 10.1111/j.1365-2702.2010.03289.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of pelvic floor musculature function during pregnancy and postpartum: a cohort study

Abstract: In clinical practice, digital vaginal palpation is effective for supporting the diagnosis of urinary, intestinal and sexual dysfunctions. Perineometry use is particularly important together with the performance of perineal exercises with biofeedback in the treatment these disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 27 publications
0
6
1
Order By: Relevance
“…Other studies investigating dyspareunia in pregnant and postpartum women found no relationship between weak PFM and dyspareunia [24,25]. Both studies had fewer women in their analysis compared to our study, 68 and 110 respectively.…”
Section: Discussioncontrasting
confidence: 42%
“…Other studies investigating dyspareunia in pregnant and postpartum women found no relationship between weak PFM and dyspareunia [24,25]. Both studies had fewer women in their analysis compared to our study, 68 and 110 respectively.…”
Section: Discussioncontrasting
confidence: 42%
“…The results of impairing PFM strength are similar to other papers' conclusions [ 18 , 20 22 ]. Nevertheless, some researchers reported PFM strength did not change significantly during pregnancy or after delivery [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Caroci et al [26] demonstrated the use of perineometry and digital vaginal palpation at the beginning of pregnancy (up to 12 weeks), at the end of pregnancy (36 to 40 weeks) and during puerperium (48 hours and 42 to 60 days postpartum) in 110 primigravidae women. For the biofeedback, the study used an electronic perineometer, which registers the potential action of pelvic floor muscle contractions and translates their intensity from visual signals.…”
Section: Resultsmentioning
confidence: 99%